Feasibility of endoscopic mucosa-submucosa clip closure method (with video) - Nishizawa, Toshihiro; Banno, Shigeo; Kinoshita, Satoshi; Mori, Hideki; Nakazato, Yoshihiro; Hirai, Yuichiro; Kubosawa, Yoko; Sunata, Yukie; Matsushita, Misako; Uraoka, Toshio (Endoscopy International Open, 2018)
Background and study aims We developed a new endoscopic closure technique using just conventional endoclips. The feasibility of endoscopic mucosa-submucosa clip closure method was evaluated in this clinical pilot study. Patients and methods This study involved consecutive 25 patients who underwent colorectal endoscopic submucosal dissection. Endoclips were placed at the edge of the mucosal defect. Each arm of the endoclip gripped the mucosa and submucosa, respectively. The direction in which the endoclip grips were placed was parallel to the short axis of the defect. Several endoclips were applied in this way. As a result, the mucosal defect was significantly reduced in size. Additional clips were placed to achieve complete closure. Results Mean size of resected specimen was 31.2 ± 11 mm. The success rate was 96 % (24/25). Mean procedure time was 9.6 ± 4.4 minutes. Mean number of endoclips was 9.3 ± 3.7. No complications were observed in any of the patients after the procedure.Conclusion Endoscopic mucosa-submucosa clip closure method could close mucosal defect of size around 2 – 4 cm completely using just conventional endoclips, and it seems easy, simple and low cost.